Long-Term Facial Nerve Outcomes after Microsurgical Resection of Vestibular Schwannomas in Patients with Preoperative Facial Nerve Palsy - Mooney, Michael A.; Hendricks, Benjamin; Sarris, Christina E.; Spetzler, Robert F.; Almefty, Kaith K.; Porter, Randall W. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives This study aimed at evaluating facial nerve outcomes in vestibular schwannoma patients presenting with preoperative facial nerve palsy.Design A retrospective review.Setting Single-institution cohort.Participants Overall, 368 consecutive patients underwent vestibular schwannoma resection. Patients with prior microsurgery or radiosurgery were excluded.Main Outcome Measures Incidence, House–Brackmann grade.Results Of 368 patients, 9 had confirmed preoperative facial nerve dysfunction not caused by prior treatment, for an estimated incidence of 2.4%. Seven of these nine patients had Koos grade 4 tumors. Mean tumor diameter was 3.0 cm (range: 2.1–4.4 cm), and seven of nine tumors were subtotally resected. All nine patients were followed up clinically for ≥ 6 months. Of the six patients with a preoperative House–Brackmann grade of II, two improved to grade I, three were stable, and one patient worsened to grade III. Of the three patients with grade III or worse, all remained stable at last follow-up.Conclusions Preoperative facial nerve palsy is rare in patients with vestibular schwannoma; it tends to occur in patients with relatively large lesions. Detailed long-term outcomes of facial nerve function after microsurgical resection for these patients have not been reported previously. We followed nine patients and found that eight (89%) of the nine patients had either stable or improved facial nerve outcomes after treatment. Management strategies varied for these patients, including rates of subtotal versus gross-total resection and the use of stereotactic radiosurgery in patients with residual tumor. These results can be used to help counsel patients preoperatively on expected outcomes of facial nerve function after treatment.
Keywords: acoustic neuroma; facial nerve; facial palsy; microsurgery; vestibular schwannoma